Performance verification of DR-PMSM for traction system according to permanent magnet shape - Chan-Bae Park; Hyung-Woo Lee; Geochul Jeong; Ik-Hyun Jo; Taehyung Kim (AIP Advances, 2020)
Unlike the conventional railway traction motor, the concept of the dual-rotor in a dual-rotor permanent magnet synchronous motor (DR-PMSM) is that two rotors are mounted on the same rotation axis, and the outer rotor and the inner rotor rotate at different speeds. The DR-PMSM can transmit the power to the wheels in a structure that can cope with various problems of the reducer systems using mechanical gear mechanisms. In this research, the design study of the inner rotor including the permanent magnet is carried out in the application of the DR-PMSM. In designing the DR-PMSM models, surface permanent magnet (SPM) type and interior permanent magnet (IPM) type are considered according to the permanent magnet type of rotor, and IPM type is designed by dividing into bar type and V type. A comparative analysis of the three 1kW-class DR-PMSM models, in terms of electromagnetic properties, is performed to assess their general performance. The overall electromagnetic properties of the three designed models are similarly derived. But, the cogging torque and the rated torque characteristics of the IPM (V) type model are the best in comparison with the other models. In addition, the 1kW-class DR-PMSM prototype with V type magnet is fabricated to verify the validity of the analytical model and performance verification is performed.